2016
DOI: 10.1371/journal.pone.0159364
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Chinese Patients with Systemic Lupus Erythematosus (SLE): A Retrospective Study of 109 Pregnancies

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease that primarily affects women during their reproductive years. The interaction between SLE and pregnancy remains debated. The objective of this study was to analyze the fetal and maternal outcomes of Chinese women with SLE. A total of 109 pregnancies in 83 SLE patients from June 2004 to June 2014 at a tertiary university hospital were reviewed retrospectively. Patients’ characteristics, clinical and laboratory data during pregnancy were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
5
28
2
2
Order By: Relevance
“…Previous studies of new-onset SLE patients during pregnancy have reported that such patients are more likely to experience kidney and blood involvement, and adverse maternal and fetal outcomes. 10,11 After comparison of new-onset with pre-existing SLE patients, our results were similar to those of previous studies. Patients with new-onset SLE who flare-up during pregnancy and have disease activity can experience adverse pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies of new-onset SLE patients during pregnancy have reported that such patients are more likely to experience kidney and blood involvement, and adverse maternal and fetal outcomes. 10,11 After comparison of new-onset with pre-existing SLE patients, our results were similar to those of previous studies. Patients with new-onset SLE who flare-up during pregnancy and have disease activity can experience adverse pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we consider that adverse fetal outcomes in new‐onset patients are same as those of active SLE patients. This finding is inconsistent with the results of previous studies . The reason for this difference between studies may relate to our choice of a different control group.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The goal of lupus treatment is to normalize renal function or at least to prevent progression of renal dysfunction (15). Precise follow up of pregnant women with lupus, treatment of complications and also prevention of teratogenic side effects is important.…”
Section: Treatmentmentioning
confidence: 99%